A fofoca como fonte de sofrimento na vida organizacional: um estudo com base na psicodinâmica do trabalho - Muniz, Alexandre (2017)
This study aims to evaluate the extent to which a gossip in the workenvironment is a source of suffering, and it is proposed to investigate its associationwith the findings of the psychodynamic theory of work. A mixed method was applied, and a qualitative research was initiallycarried out to understand some aspects about the phenomenon of gossip in Brazil,obtaining testimony from 25 professionals, which allowed the delineation ofinvestigation categories through the analysis of content. A quantitative study wascarried out to evaluate the mediating impact of gossip on the pathogenic suffering, itsrelationship with physical, social and psychological damages of individuals at work, aswell as to validate the causal relations proposed by the work psychodynamics in Brazil.Through a questionnaire answered by 372 professionals, the categories were modeledinto factors through structural equations.The research results pointed out that gossip in the workplace increases theeffect of the work context on pathogenic suffering. He also revealed that individualswith lower the education level have more difficulty in dealing with rigid organizationalenvironments. In turn, the premises of work psychodynamics were confirmed,especially the conclusions of the Brazilian school, elucidating the high psychologicalimpact resulting from the work.The study did not focus on the relationship between gossipand subjective mobilization, to draw a parallel with individuals' strategy for dealing withthe harmful environment. This perspective can be explored in future studies. This study contributes to the debate on the topic of gossipand suffering in organizations, considering the incipient academic production.Social Implications - Elucidating the impacts of harmful phenomena that affect healthand people's lives, this study contributes to overcoming degraded work environments. This is the first study done in Brazil about gossip and suffering withoutwork.